POTENTIAL OF CASHEW NUT SHELLS IN BIO-BRIQUETTES PRODUCTION IN ADDRESSING HOUSEHOLD HEATING AND COOKING ENERGY DEMAND IN TANZANIA (The Journal of Building and Land Development, 2024)
ABSTRACT Poor disposal of cashew nut shells contributes to environmental pollution through release of greenhouse gases from their decomposition and burning processes in open dumps. This research explores the potential of transforming cashew nut shells, initially considered waste, into bio-briquettes for household heating and cooking. Cashew nut shells were squeezed using an electric-operated pressing machine to obtain the grits and oil. The study analyzed cashew nut shell grit's combustible properties using proximate analysis and emission tests, and established higher heating values based on the proximate analysis. The proximity test revealed that cashew nut grits have high volatile solids (71.48%), low ash content (2.32%), low moisture content (8.18%) and average fixed carbon (18.01%), indicating potential emissions due to their high volatile solids (VS) value. Higher heating values of cashew nut shell grit was 17.49 MJ/Kg, lower than other studies' values of 20.78KJ/Kg and 27.73KJ/Kg for non-carbonized and carbonized cashew nut shell grits-cake, respectively and 21.9KJ/Kg for coffee husks. Regardless of low higher heating value compared to other feedstock, bio-briquettes produced using cashew nut shells grits can be utilized for household heating and cooking in their original state. Their quality can be enhanced by adding a carbonization process to increase fixed carbon and thereafter higher heating values.Â Keywords: Cashew nut shells, Bio-briquettes, Charcoal, Firewood and Energy